2007
DOI: 10.1111/j.1537-2995.2007.01488.x
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation function in fresh‐frozen plasma prepared with two photochemical treatment methods: methylene blue and amotosalen

Abstract: BACKGROUND:Pathogen inactivation of plasma intended for transfusion is now the standard of care in Belgium. Two methods for treatment of single plasma units are available: amotosalen plus ultraviolet A light and methylene blue plus visible light. This study compared the quality and stability of plasma treated with these two methods. STUDY DESIGN AND METHODS: Plasma units made from a pool of two ABO-matched fresh apheresis units were photochemically treated with either amotosalen (PCT-FFP) or methylene blue (MB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
46
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 34 publications
8
46
2
1
Order By: Relevance
“…As published by others [3,6,24,25], some losses of the functional activities of the coagulation factors FI, FV, FVIII and FXI were found. However, the average loss did not exceed 20% for any of the investigated parameters.…”
Section: Discussionsupporting
confidence: 53%
“…As published by others [3,6,24,25], some losses of the functional activities of the coagulation factors FI, FV, FVIII and FXI were found. However, the average loss did not exceed 20% for any of the investigated parameters.…”
Section: Discussionsupporting
confidence: 53%
“…Osselaer et al found that losses of fibrinogen, FV, FVIII, FXI, and Protein S activities were greater for MB-FFP than AS-FFP, although the most affected proteins, fibrinogen and FVIII, still retained 70–80% of their FFP activity levels after treatment and freezing and thawing of MB-FFP. The authors noted that the mean values for all 18 plasma protein activities tested fell within normal references ranges in all cases and that ADAMTS-13 was unaffected by either PR treatment [84]. Backholer et al reported similar findings in another paired comparison in which FV, FXI, FXIII, and fibrinogen losses were significant for MB-FFP, but not for AS-FFP, by analysis of variation (ANOVA) of FFP, MB-FFP, and AS-FFP; six other coagulation factors were unaffected by either treatment [85].…”
Section: Overview: Assessing the Quality Of Transfusable Plasmamentioning
confidence: 99%
“…The process has been validated in blood centers to verify the performance of the PCT system under different routine operating conditions [18,19]. These centers' validations demonstrated that coagulation factor levels meet European and national standards and the product has a very good performance in routine use.…”
Section: Intercept Proceduresmentioning
confidence: 98%